CHEMICAL AND AMINO ACID COMPOSITION OF QUAIL MEAT FOR FEEDING DISTILLERS DRIED GRAIN WITH SOLUBLES - I.I. Ibatullin; A. Yu. Plyska; M. Yu. Sychov (Тваринництво та технології харчових продуктів, 2020)
An actual problem today is the utilization of waste products of the processing industry by feeding them to animals in order to obtain valuable animal protein. With this aim, a scientific and economic experiment was conducted to determine the productivity effect of table poultry young quails feeding with distillers dried grain (DDGS) in the composition of feed in the amount of 5–20 % per the productivity and chemical composition of their meat. At the beginning of the experiment, the daily young quails of the Pharaoh breed were divided into 5 groups according to the principle of analogues where the 1st one was the control and the 2nd–5th were the experimental ones. In the compound feed of animals of the 1st control group the distillers dried grain (DDGS) was absent. Animals of the 2nd experimental group consumed compound feed with a content of 5 % distillers dried grain (DDGS), the 3rd experimental group – 10 %, the 4th experimental group - 15% and the 5th experimental group – 20 % of the specified feed. The article presents the results of a scientific and economic trial to determine the effect of feeding 5–20 % of distillers dried grain (DDGS) to young broiler quail in the composition of compound feeds on the productivity and chemical composition of their meat. It is proved that the highest productivity of quail is achieved by consuming 10% of distillers dried grain (DDGS) in the compound feed. The doses of DDGS by 5 and 15 % also has a positive effect on the live weight of quails. However, analysis of the chemical and amino acid composition of the meat has shown that already at the content of 10 % of DDGS in the compound feed in the quail meat a decrease in protein and an increase in the proportion of fat. It is worth noting the constant level of raw ash in the meat of quails of all groups. Increasing the distillers dried grain with solubles (DDGS) content of the compound feed also contributes to the reduction of some essential amino acids. However, changes in the chemical and amino acid composition of quail meat during distillers dried grain (DDGS) feeding were not statistically significant. Thus, the optimal content of distillers dried grain (DDGS) in the feed of table poultry quails can be considered as 5–10 %